Mujer y abogacía en la Roma Antigua: tres casos célebres - Truque Morales, Ana Lucía (2016)
While men held the dominant position in ancient Rome and women were not allowed to hold public office, there were periods when women were able to act as attorneys before the courts. Several authors tell about famous cases in which women like Amaesia Sentia and Hortensia served as lawyers, and they also record the history of Caya Afrania, whose temper allegedly caused the edict which forbade women to represent other persons before the courts.